A comparison of the rate and accuracy of symbol location on visual displays using colour-coded alphabetic and categorisation strategies in Grade 1 to 3 children - Uys, C.J.E. (Catharina Jacoba Elizabeth) (University of Pretoria, 2013)
Thesis (PhD)--University of Pretoria, 2012.